2009
DOI: 10.1097/ta.0b013e318184205c
|View full text |Cite
|
Sign up to set email alerts
|

Defining Impairment and Treatment of Subacute and Chronic Fractures of the Coracoid Process

Abstract: In the overlooked and untreated type I fracture with persistent pain and functional impairment, reduction and fixation of the coracoid fracture aimed at reconstruction of the firm scapuloclavicular connection and structural restoration of the coracoacromial arch results in gratifying outcomes. In the cases of type II fracture, conservative treatment is indicated. When presenting with atypical manifestations of subcoracoid impingement, releasing of the coracoacromial ligament proves effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…A variety of treatment algorithms to address coracoid fractures have been well described, with conservative treatment being the most common choice. 3,7,[25][26][27] Operative treatment is typically reserved for Eyres types IV and V coracoid fractures occurring at the base of the coracoid and either the body of the scapula or the glenoid fossa. 7,28 In the present case, the patient was initially treated for a coracoid fracture and a minor anterior subluxation event nonoperatively with a bone stimulator, which resulted in excellent callus and full return to play during the same season.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of treatment algorithms to address coracoid fractures have been well described, with conservative treatment being the most common choice. 3,7,[25][26][27] Operative treatment is typically reserved for Eyres types IV and V coracoid fractures occurring at the base of the coracoid and either the body of the scapula or the glenoid fossa. 7,28 In the present case, the patient was initially treated for a coracoid fracture and a minor anterior subluxation event nonoperatively with a bone stimulator, which resulted in excellent callus and full return to play during the same season.…”
Section: Discussionmentioning
confidence: 99%
“… 1-3 Ogawa et al classified these fracture according to their relationship to the CCL: type I fractures occur proximally and type II fractures distally to the attachment of the CCL. 4 Both fractures are suggested to be avulsion fractures. Type I fractures are caused by pulling force of the CCL and type II by muscular violence of the short head of biceps, the coracobrachialis and the pectoralis minor.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Associated AC joint dislocations are reported in more than 50% of coracoid fractures. 4 The few studies suggest a difference between adolescent and skeletally mature patients with regard to this injury pattern. Since in adolescent the CCL are stronger than the attachment of the epiphyseal plates, the forces will result in an avulsion of the coracoid process, 12 whereas in the mature skeleton, the coracoid process and the clavicle are stronger than the CCL complex, resulting in an AC dislocation without coracoid fracture, but with CCL disruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in patients who had complications due to dislocations of the acromioclavicular joint, clavicle fracture or reductions of the shoulder joint, surgical treatment was the best choice [9]. Ogawa et al [10] suggested that for the patients with Ogawa type II fraction, early physical therapy and simply suspension of the index arm was recommended. However, conservative treatments induced non-union of the fracture or pseudarthrosis of the coracoid.…”
Section: Introductionmentioning
confidence: 99%